Ali Ibn Abbas / Haly Abbas and the Transmission of Perso-Islamic Medicine to the West - Shahram Jalilian; Mahnaz Sadat Mortazavi (Journal of Research on History of Medicine)
Iranian physicians stood at the forefront of medical innovation during the Islamic Golden Age of Medicine (9-11 CE). They played a pivotal role in the development and prosperity of medicine within the Muslim empire through their extensive contributions to written masterpieces, significantly enriching the medical knowledge of the era. Furthermore, they helped Western medical traditions flourish by translating these works into Latin. ʻAlī ibn al-ʻAbbās al-Majūsī al-Arrajānī, known in the West as “Haly Abbas,” was one of the Iranian physicians of the era. His only work, Kitāb Kāmil al-ṣināʻah al-ṭibbīyah or al-Malakī (The Royal Book), was a great medical encyclopedia that delved into both theoretical and practical aspects of medicine – which was considered the most comprehensive book on Persian Medicine before Avicenna’s al-Qānūn. Al-Malakī played a pivotal role in medical education across the Muslim world and Europe. This study is based on a library research method, drawing from a thorough review and analysis of relevant sources.